Improving toughness of medium-Mn steels after friction stir welding through grain morphology tuning. (10th August 2022) - Jeong, Mun Sik; Park, Tak Min; Kim, Dong-Il; Fujii, Hidetoshi; Im, Hye Ji; Choi, Pyuck-Pa; Lee, Seung-Joon; Han, Jeongho
Highlights: The FSW steel showed a higher toughness than the TIG-welded steel and base material. Morphology tuning by FSW eliminates a weak prior γ boundary and improves the toughness. The preserved γR grains after FSW contribute to the improved toughness by active TRIP. Abstract: This work demonstrated the viability of friction stir welding for the welding of medium-Mn steels when used as cryogenic vessel materials for liquefied gas storage. We used an intercritically annealed Fe-7Mn-0.2C-3Al (wt.%) steel with a dual-phase ( α ′ martensite and γ R retained austenite) nanolaminate structure as a base material and systematically compared its microstructure and impact toughness after friction stir and tungsten inert gas welding. The friction stir welded specimen exhibited a large amount of γ R phase owing to a relatively low temperature during welding, whereas the tungsten inert gas welded specimen comprised only the α ′ phase. Furthermore, the friction stir welded steel exhibited a tuned morphology of nanoscale globular microstructure at the weld zone and did not exhibit any prior austenite grain boundary due to active recrystallization caused by deformation during welding. The preserved fraction of γ R and morphological tuning in the weldment improved the impact toughness of the friction stir welded steel at low temperatures. In the steel processed by tungsten inert gas welding, the notch crack propagated rapidly along the prior austenite grain boundaries—weakened by Mn and P segregations—resulting in poor impact toughness. However, the friction stir welded steel exhibited a higher resistance against notch crack propagation due to the slow crack propagation along the ultrafine ferrite/ferrite ( α / α ) interfaces, damage tolerance by the active transformation-induced plasticity from the large amount of γ R, and enhanced boundary cohesion by suppressed Mn and P segregations. Graphical Abstract: Graphical Abstract Image, graphical abstract .